2020
DOI: 10.1002/ldr.3813
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of temporal and spatial changes of global ecosystem health

Abstract: Understanding the spatial distribution pattern and driving factors behind ecosystem health is beneficial to ecosystem management and restoration. However, the literature shows little in‐depth exploration of regional heterogeneity and the factors that influence ecosystem health on a global scale. This study assesses global ecosystem health for the period 2000–2015 based on the vigor, organization, resilience, and service (VORS) model, and it explores the factors that influence regional differences in ecosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…This result indicates that population and water resources are the main factors that influence the spatial differentiation of ecosystem health in the YRB. The study's conclusion is consistent with the findings of Cao et al [91], Ran et al [92], He et al [76], and Xu Ye et al [39]. High population density increases the demand for ecosystem services, thereby bringing pressure on the natural ecosystem and affecting the ecosystem health.…”
Section: Factors That Influence Ecosystem Healthsupporting
confidence: 90%
See 2 more Smart Citations
“…This result indicates that population and water resources are the main factors that influence the spatial differentiation of ecosystem health in the YRB. The study's conclusion is consistent with the findings of Cao et al [91], Ran et al [92], He et al [76], and Xu Ye et al [39]. High population density increases the demand for ecosystem services, thereby bringing pressure on the natural ecosystem and affecting the ecosystem health.…”
Section: Factors That Influence Ecosystem Healthsupporting
confidence: 90%
“…The result shows that the combined effect of population density and rainfall can enhance the explanatory ability with regard to the spatial heterogeneity of watershed ecosystem health. Ran et al [92] and He et al [76] observed a similar phenomenon. The meteorological and socio-economic factors exert synergistic effects on ecosystem health changes and can be mutually enhanced.…”
Section: Factors That Influence Ecosystem Healthmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition to human activists, natural factors influenced the ecological integrity condition of Alxa Left. Related studies have shown that the ecological environment of desert ecosystems is deeply influenced by climate factors (Clarke and Rendell, 1998;Ran et al, 2021). In our study, climate factors, including precipitation, temperature and potential evapotranspiration had a great effect on the ecological integrity of Alxa Left.…”
Section: Driving Factors Of Ecological Integritymentioning
confidence: 52%
“…Many scholars have constructed ecosystem health evaluation index systems using various models: PSR [26,27], Drive-Pressure-State-Impact-Response [28], VOR [29], and Basic-Pressure-State-Response [30]. In addition, multi-scale studies to evaluate ecosystem health have been carried out at global, provincial, and municipal scales [31][32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%